A sensitive EUV Schwarzschild microscope for plasma studies with sub-micrometer resolution - Zastrau, U; Feigl, T; Appel, K; Chen, B; Fletcher, LB; Förster, E; Gamboa, E; Gericke, DO; Göde, S; Grote-Fortmann, C; Hilbert, V; Kazak, L; et al. (AIP Publishing, 2018)
We present an extreme ultraviolet (EUV) microscope using a Schwarzschild objective which is optimized for single-shot sub-micrometer imaging of laser-plasma targets. The microscope has been designed and constructed for imaging the scattering from an EUV-heated solid-density hydrogen jet. Imaging of a cryogenic hydrogen target was demonstrated using single pulses of the free-electron laser in Hamburg (FLASH) free-electron laser at a wavelength of 13.5 nm. In a single exposure, we observe a hydrogen jet with ice fragments with a spatial resolution in the sub-micrometer range. In situ EUV imaging is expected to enable novel experimental capabilities for warm dense matter studies of micrometer-sized samples in laser-plasma experiments.